Monetary and Exchange Rate Policy of Transition Economies of Central and Eastern Europe after the Launch of EMU - Masson, Paul (IMF Policy Discussion Papers; Policy Discussion Paper ;, 1999)
The more advanced Central and Eastern European Countries (CEECs) face an evolving set of considerations in choosing their exchange rate policies. On the one hand, capital mobility is increasing, and this imposes additional constraints on fixed exchange rate regimes, while trend real appreciation makes the combination of low inflation and exchange rate stability problematic. On the other hand, the objectives of EU and eventual EMU membership make attractive a peg to the euro at some stage in the transition. The paper discusses these conflicting considerations, and considers the feasibility of an alternative monetary framework, inflation targeting.